The Influence of Work-Life Balance, Digital Competence, and Emotional Intelligence on Teacher Performance (A Study on Teachers of SMK Kartika X-2 Jakarta, Pesanggrahan, South Jakarta) - Khairunnisa, Syifa; Kuncoro, Aris Wahyu (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the impact of work-life balance, digital competence, and emotional intelligence on teacher performance in vocational schools in Indonesia. The research emphasizes how the ability to balance personal and professional responsibilities, mastery of digital skills, and the capacity to manage emotions contribute to the effectiveness and productivity of teachers. A quantitative approach was employed, and data were collected through structured questionnaires distributed to teaching staff. The analysis used multiple regression techniques to test the proposed relationships among variables. The findings reveal that work-life balance, digital competence, and emotional intelligence positively and significantly influence teacher performance. These results highlight the importance of supporting teachers in achieving harmony between work and personal life, enhancing digital literacy, and strengthening emotional regulation. The study provides both theoretical contributions to human resource management in education and practical implications for improving the quality of vocational school performance in Indonesia.